You can run, but you will never escape: A new species of Psyllaephagus Ashmead (Hymenoptera, Encyrtidae), parasitoid of the classical biological control agent Boreioglycaspis melaleucae (Moore) (Hemiptera, Aphalaridae) in Florida, USA - Alana R. McClelland; Matthew R. Moore; Jonathan S. Bremer; Elijah J. Talamas; Susan E. Halbert; Virgine T. Singarayan; Bradley T. Brown; Matthew F. Purcell; Dean R. Brookes; Matthew G. Hentz (Journal of Hymenoptera Research, 2025)
Melaleuca quinquenervia (Cav.) S.T. Blake (Myrtales: Myrtaceae) is an invasive tree in Florida, USA, for which a psyllid, Boreioglycaspis melaleucae (Moore) (Hemiptera: Aphalaridae), was successfully established in April, 2002 to control its spread. A parasitoid wasp, Psyllaephagus migrator McClelland, sp. nov. was found to parasitize this psyllid in Australia, which we consider to be its native range, and in Florida, where we consider it to be adventive. We provide a description, high resolution images and morphological diagnosis for P. migrator and a molecular data set of five gene regions to facilitate its identification and use in phylogenetic studies. The biology of the parasitoid is presented with documentation of its immature stages. Trapping data suggest that P. migrator has reduced populations of the biocontrol agent B. melaleucae in Florida.